(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The range of fats and oils suitable for fatliquoring fur skins is significantly wider than the range of fats suitable for sueding leather. Fat tanning is usually combined with other tanning methods, such as pickling, grain tanning with aluminum alum, chrome tanning, formalin tanning, quebrach tanning, etc., and therefore this process is never performed independently. It consists of tanning the skins according to the following procedure: Using another method, the hide is coated on the flesh side with fat or oil, or even better, a fat emulsion, then left to dry for 6 to 12 hours, followed by the usual processes.